Spin the wheel: Playfulness in sexually transmitted infections (sti) prevention workshops (Revista Contexto & Educação, 2026)
Introduction: The Bonde Universitário extension project promotes actions aimed at preventing Sexually Transmitted Infections (STIs). Given the limited discussion on the topic, knowledge about STIs remains incipient, making it necessary to develop activities that expand access to information in diverse settings. Objective: To report the experience of undergraduate students in the development of a care technology for STI prevention. Methodology: This experience report describes the creation and application of the Prevention Wheel, a playful tool developed by undergraduate students for educational actions on STIs. The methodology included brainstorming, planning, execution, and evaluation of the activity. All activities involved the participation of students and undergraduate extension members. The development of the wheel and its entire design were intentionally planned to attract attention and encourage interaction. The Prevention Wheel aims to promote exchange among participants and foster dialogue. It consists of a circular wooden structure fixed to a base that allows support and rotation. Throughout the structure, there are colored cards containing various questions, and the activity consists of spinning the wheel and drawing a question for discussion. Results: When the wheel was spun, the selected color included questions on the following topics: concept and types of STIs, combined prevention strategies, rapid testing, treatments, and health promotion. In addition to discussions, the activity included the distribution of gifts, prevention supplies, and educational pamphlets. The Prevention Wheel attracted people to the educational actions, generating curiosity and receptiveness. When faced with the questions on the cards, participants were encouraged to share knowledge, doubts, and curiosities. Guidance on STI prevention and education on sexual and reproductive health were central actions, enabling the dissemination of knowledge. Conclusions: The use of playful activities during extension actions is important, as it motivates the participation of the target audience. The Prevention Wheel made the learning process light, dynamic, and engaging, contributing to awareness-raising. The students’ experience in creating and applying this tool demonstrates the applicability of innovative approaches in health.
Keywords: Health education; Sexually transmitted infections; Population health